Routes of Wandering : Nomadism, Voyages and Transitions in Contemporary Israeli Art. - Jabès, Edmond; Shapira, Sarit (Jerusalem : The Israel Museum, 1991)
Abramson, Larry ; Aroch, Arich ; Bar El, Ido ; Bar-Lev, Jenifer ; Borkovsky, Joshua ; Cohen Gan, Pinchas ; David, Nurit ; Danziger, Yitzhak ; Druks, Michael ; Efrat, Benni ; Fainaru, Belu-Simion ; Frydlander, Barry ; Gershuni, Moshe ; Gitlin, Michael ; Klasmer, Gabi ; Kupferman, Moshe ; Lichtenberg Ettinger, Bracha ; Luski, Aïm ; Maor, Haim ; Ninio, Moshe ; Neustein, Joshua ; Semah, Joseph ; Sgan-Cohen, Michael ; Ullman, Micha
Routes of Wandering : Nomadism, Voyages and Transitions in Contemporary Israeli Art, The Israel Museum, Jerusalem, 191
boek
Keywords: Israel